The Influence of Financial Literacy and Lifestyle on Financial Behavior of Management Students of the College of Economics Enam Enam Kendari - Chaterina Monica Idelberth; Ibnu Hajar; Nofal Supriaddin (PT. Hafasy Dwi Nawasena, 2025)
This study aims to find out and analyze: 1) The influence of financial literacy and lifestyle on the financial behavior of STIE Enam Enam Kendari Management students, 2) The influence of financial literacy on the financial behavior of STIE Enam Enam Kendari Management students, 3) The influence of lifestyle on the financial behavior of STIE Enam Enam Kendari Management students. The approach used in this study is a quantitative approach. The population in this study is 60 students of STIE Enam Enam Kendari. Sampling in this study was using the slovin formula. The data analysis used was using descriptive analysis and the Statistical Package for the Social Sciences (SPSS). The results of the study show that; 1) Financial literacy and lifestyle simultaneously have a positive and significant effect on the financial behavior of STIE Enam Enam Kendari students, 2) Lifestyle has a positive relationship and has a significant effect on financial behavior, 3) Financial literacy has a positive relationship and has a significant effect on financial behavior.